Intel Makes A Big Jump In Computer Math. - Moore, S.K (IEEE spectrum)
With Intel's new crop of 45-nanometer processors, code-named Penryn, the company is making the first substantial upgrade in its processors' divider since the original Pentium came out in 1993. The speedup doubles the number of bits calculated with each tick of the processor's clock and will make a substantial difference to financial and scientific computing. And because Intel powers so much of the computer market, the development could tempt programmers to retreat from the less accurate but faster software tricks they've used as a substitute for division.